Assessment of Patient Satisfaction towards Dental Care Services Provided at Private Dental Hospital: Cross Sectional Study - Muhammad Abdullah, Ayma Syed, Fariha Rizwan, Mariam Rabya Sultana, Muhammad Rizwan Saghir, Waqas Latif (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The dental practice is a mixture of science and art that provides excellent dental and oro-facial care to their patients. Aim: To assess the level of patient satisfaction and seek improvement in the quality of dental services provided at Private Hospital. Study Design: Cross sectional study. Methodology: A total number of 400 patients were enrolled who responded to the questionnaire. The ethical approval was obtained from hospital review ethical committee, after completing and submitting the research proposal. The questionnaires were filled by patients after being guided by dental assistants for accuracy and complete filling of data. Results: Among 400 enrolled subjects, there were 53.7% females while males were 46.3%. Satisfaction score was higher in all domains except reception desk & waiting area. No significant difference was observed in satisfaction score of patient-doctor interaction, dental assistant patient interaction and overall health facility domain among different age groups. The satisfaction score of reception desk & waiting area domain was significantly lower in young patients (<30years). There was no significant difference in satisfaction score of all domains between both genders. Patient visited to Orthodontics department had lower score in dental assistant patient interaction domain as compared to patients visited operative department. Similarly, overall satisfaction score of the patients visited Orthodontics department was scored lower as compared to remaining departments. Conclusion: It was concluded that there was significantly high satisfactory score from patients. Thus, were ready to re-visit the hospital. Young patients were less satisfied pertaining reception desk services and waiting area. Patients visited Orthodontics department were also less satisfied with the behavior of dental assistant.